Change in Incidence and Epidemiology of Inflammatory Bowel Disease in 2- to 9-Year-olds in Southwest England. Issue 5 (November 2021) - Fernandes, Sofia; Spray, Christine H.; Whitmarsh, Alex; Sandhu, Bhupinder K.; Wiskin, Anthony E.
ABSTRACT: Objectives: The aim of the study was to characterize epidemiology, phenotype, and clinical outcome of Inflammatory Bowel Disease (IBD) diagnosed ages 2 to 9 years, and compare age groups 2 to 5 and 6 to 9 years. Methods: A population-based retrospective cohort study of all <10-year-olds diagnosed with IBD between 2004 and 2017 in Southwest England was performed. Patients were divided into age groups at diagnosis. Demographics, investigations, and phenotype at diagnosis were collected. Treatments and outcomes were analysed at 1, 2, 5, and 10 years follow-up. Poisson regression was used for IBD incidence rate ratios; Wald test for variation by age group; parametric/nonparametric tests for phenotype. Results: There were 666 new paediatric IBD (pIBD) patients ages ⩽16 years, from which 136 were 2 to 9 (2–5 years: 32; 6–9 years: 104). Incidence of pIBD increased from 4 to 6 cases per 100, 000 whereas in A1a group was stable around 2 cases per 100, 000. Crohn Disease (CD) children were majority boys, 2- to 5-year-olds were more likely to have ileal sparing than 6 to 9-year group but had similar rates of surgery and anti-TNF therapy. Two- to 5-year-olds with ulcerative colitis were more likely to have surgery but rates for anti-TNF therapy were similar. Sixteen percent of 2- to 5-year-olds and 10% of 6- to 9-year-olds had IBD-unclassified. No significant differences in symptoms or time to diagnosis were found. Conclusions: Twenty percent of pIBD in Southwest England are 2 to 9 years old. pIBD incidence has increased but is stable in that group. In terms of phenotypic differences, ileal sparing in CD and pancolitis and surgery in UC, are more likely in 2- to 5-year-olds.